Teachers’ perceptions of the influence of awards received for excellence in teaching early in their careers - Ballew, M. Jean (Kansas State University, 2012)
This study sought to provide insight regarding how novice teachers perceive the influence of receiving an award for excellence early in their careers. The questions guiding this study focus on the perceptions of the respondents regarding whether or not they perceived that the award was motivating; whether the award influenced them personally, professionally, and organizationally; and whether they perceived an increase in commitment to the profession. This quantitative study gathered data from an on-line questionnaire sent to teachers who received the Kansas Horizon Award from 2003 through 2011. The study used exploratory factor analysis, descriptive statistics, and analysis of variance procedures to ascertain whether or not there was any significance regarding the way awardees responded to 15 Likert items. The data were compared to six demographic variables: year of award; age of winner at the time of the award; level taught – elementary or secondary; location of school – urban, suburban, or rural; gender; and teaching status. Each of the 15 Likert items were aligned with one of the four factors identified by the factor analysis – internal influence, expectations, external influence, and commitment to the profession. The significant statistics from the factor analysis ranged from .506 through .900. The analysis of variance showed significance for three factors and variables.(1) The most recent awardees (2009-2011) perceived a greater influence from the award regarding expectations (p = .03) than did those teachers who won the award in previous years. (2) Teachers from urban schools perceived a greater significance from the award regarding external influence (p = .05) than those from suburban schools. (3) Females perceived a greater influence from the award than did males regarding commitment to the profession (p = .03). Recommendations for practice include the need for increased awareness of administrators regarding the importance of awards and recognition for teachers, increased support for teacher attendance at the state conference, and increased leadership opportunities for awardees. Recommendations for further research include studies of how administrators choose nominees for awards and why some never nominate anyone, the relationship between leadership opportunities and awards, and retention of award-winning teachers.
Keywords: Awards; Novice teachers; Excellence in teaching; Self-efficacy; Motivation; Educational Administration (0514); Educational leadership (0449); Education, General (0515)